Satellite remote sensing, GIS and sun-photometers for monitoring PM 10 in Cyprus: issues on public health - Hadjimitsis, Diofantos G.; Nisantzi, Argyro; Themistocleous, Kyriacos; Trigkas, Vasillis; Matsas, Alexandros (My University, 2010)
PM 10 and PM 2.5 particles are very significant issues for the public health of the community. Such parameters are measured from air-pollution stations that are scarcely distributed in the Cyprus region. Satellite remote sensing can provide synoptic coverage of the Cyprus area either daily from MODIS sensor or every 16 days from Landsat. Sunphotometers are used to measure the aerosol optical thickness (AOT) on ground during the satellite overpass. Several different campaigns have been made both for two urban areas in Paphos and Limassol area. For the period 28/10/09 - 30/12/09, the regression analysis between PM 10 and PM 2.5 for the Paphos town (central) gave coefficient of determination of R 2=0,78 and R 2=0,61 respectively. Coefficient of determination R 2 =0.61 was found for the period May-June 2009 for the centre of Limassol when PM10 was regressed against AOT measured from MICROTOPS handheld sun-photometer. The AOT data retrieved from MODIS AOT (at 550 nm) and CIMEL sun-photometer (AERONET) also provided a high correlation (r=0.9, R2 = 0.81) for the centre of Limassol for April to July 2010 measurements. Results obtained by correlating MODIS AOT (at 550 nm) against hand-held MICROTOPS sun-photometer in the centre of Limassol for the period January 2009 to March 2010 gave R 2=0,81. Using the PM10 limit of 50μg/m 3 as prescribed by the European Union and the regression model found for the Limassol area, a threshold value of AOT for this area of 0.6 was found. Such value can be used as threshold AOT values for alerts either using the MODIS or Landsat satellite imagery. An example of how a GIS can provide temporal variations of AOT over the Cyprus area is shown
Keywords: AERONET; Air pollution; Aerosol optical thickness; CIMEL sun-photometer; GIS; Landsat; Microtops sun-photometer; MODIS; PM10; PM2.5; Public health